Membangun Iman Kristen di Kalangan Suku Dayak Kanayatn Melalui Pendekatan Kontekstual Upacara Adat Kamang Tariu - Nianda Nianda; Theodorus Theodorus; Giri Krispambudi; Yuliawati S. (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), 2022)
In general, the customs, traditions and culture of each ethnic group differ depending on the geographical location and the way of life of each. Almost all customs and cultural traditions of each ethnic group become a benchmark for ethics, morals and habits that occur and are always positive according to their ethnicity, although there are some other cultural views that consider it not necessarily positive. For the Dayak Kanayatn tribe, traditions, customs and culture are the most important things in managing daily life. Dayak Kanayatn is very thick with tradition and culture. One of the most feared Dayak traditions is the